Caracterização da fauna de crustáceos decápodes no entorno da Comunidade do Curral Grande, Monte Alegre (Pará, Brasil) - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2017)
Studies on the biodiversity of crustaceans in ecosystems are important not only for the establishment of databases on this biodiversity, but also as tools that can help in the construction of processes and guidelines that will guide the sustainable use of natural resources, integrating traditional uses of these riches by the local population. Therefore, the present study aimed to survey the decapod crustaceans fauna in the surroundings of the community of Curral Grande, in the municipality of Monte Alegre-PA, in two streams and a lake evaluating if these environments present differences in their composition. The animals were collected in four sampling stations, georeferenced with the aid of a GPS device (GARMIN) in two periods, in the months of July and September of 2017. The results showed the presence of two shrimp species of the family Palaemonidae (Macrobrachium amazonicum and Macrobrachium ferreirai) and a crab species of the family Trichodactylidae (Dilocarcinus pagei). Although it was possible to identify only three species of crustaceans, due to the short period and the small sample area, the work contributed to a greater knowledge in the area of decapod crustaceans, since these animals had not yet been identified in the region of Monte Alegre-PA.
Keywords: Crustáceos; Decápodes; Igarapés; Amazônia; CNPQ:: CIÊNCIAS BIOLÓGICAS